Silica–gold bilayer-based transfer of focused ion beam-fabricated nanostructures. Issue 39 (23rd September 2015) - Wu, Xiaofei; Geisler, Peter; Krauss, Enno; Kullock, René; Hecht, Bert
Abstract : Ex and in situ transfer of FIB-fabricated nanostructures are demonstrated by transferring plasmonic nano-antennas to silicon wafers and scanning probes. Abstract : The demand for using nanostructures fabricated by focused ion beam (FIB) on delicate substrates or as building blocks for complex devices motivates the development of protocols that allow FIB-fabricated nanostructures to be transferred from the original substrate to the desired target. However, transfer of FIB-fabricated nanostructures is severely hindered by FIB-induced welding of structure and substrate. Here we present two ( ex and in situ ) transfer methods for FIB-fabricated nanostructures based on a silica–gold bilayer evaporated onto a bulk substrate. Utilizing the poor adhesion between silica and gold, the nanostructures can be mechanically separated from the bulk substrate. For the ex situ transfer, a spin-coated poly(methyl methacrylate) film is used to carry the nanostructures so that the bilayer can be etched away after being peeled off. For the in situ transfer, using a micro-manipulator inside the FIB machine, a cut-out piece of silica on which a nanostructure has been fabricated is peeled off from the bulk substrate and thus carries the nanostructure to a target substrate. We demonstrate the performance of both methods by transferring plasmonic nano-antennas fabricated from single-crystalline gold flakes by FIB milling to a silicon wafer and to a scanning probe tip.